(untitled) - Rees, Abraham (North Pomfret, 1972)
This volume covers seventy-three subjects from Cements and Lutes to Fly, and includes sections of plates illustrating Cotton Manufacture, Cutlery, Cutting- Engine, Docks and Engines. (See back panel for complete list of contents.)...
Keywords: Quy trình sản xuất,Manufacturing processes